2022
DOI: 10.1111/pbi.13922
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate transporter BnaBASS2 impacts seed oil accumulation in Brassica napus

Abstract: Bile acid: sodium symporter family protein 2 (BASS2) is a sodium-dependent pyruvate transporter, which transports pyruvate from cytosol into plastid in plants. In this study, we investigated the function of chloroplast envelope membrane-localized BnaBASS2 in seed metabolism and seed oil accumulation of Brassica napus (B. napus). Four BASS2 genes were identified in the genome of B. napus. BnaA05.BASS2 was overexpressed while BnaA05.BASS2 and BnaC04.BASS2-1 were mutated by CRISPR in B. napus. Metabolite analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In the parallel transcriptomic analysis, glycolytic pathway genes were significantly upregulated, including the GAPDH , PK , and BASS genes. It is reported that Bass2 can increase the oil content of Brassica napus [ 33 ]. Some researchers have revealed that GAPCs can regulate the accumulation of seed oil content [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the parallel transcriptomic analysis, glycolytic pathway genes were significantly upregulated, including the GAPDH , PK , and BASS genes. It is reported that Bass2 can increase the oil content of Brassica napus [ 33 ]. Some researchers have revealed that GAPCs can regulate the accumulation of seed oil content [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exhibited that glycolysis metabolites are closely related to seed oil content, such as fructose-6-phosphate (F6P), glucose-6-phosphate (G6P) and fructose-1,6-diphosphate (FBP), etc. [ 33 ]. In the TMHO vs. TMLO and MHO vs. MLO comparison groups, we also found that glycolysis metabolites were enriched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the parallel transcriptomic analysis, glycolytic pathway genes were signi cantly unregulated, including the GAPDH, PK, and BASS genes. It is reported that Bass2 can increase the oil content of Brassica napus [35]. Some researchers have revealed that GAPCs can regulate the accumulation of seed oil content [36].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 212 subnetworks were identi ed in the FMHO vs. FMLO comparison group. Multiple studies have demonstrated that genes and metabolites related to the glycolysis pathway affect the accumulation of plant oil [35,41]. Glycolysis is core to the synthesis of oil, as it converts sugars into precursors for the synthesis of fatty acids [41].…”
Section: Discussionmentioning
confidence: 99%